Leaf trichomes in Senecio section Mulgediifolii (Senecioneae, Asteraceae) - Rojas-Leal, Alicia; Villaseñor, José Luis; Terrazas, Teresa (Instituto de Ecología, A.C., 2017)
Background and Aims: A study of trichome complements in Senecio section Mulgediifolii using light and scanning electron microscopy was carried out, with the aim of distinguishing characters that contribute to identify their species.Methods: The middle section of the leaf lamina was collected in the field or taken from herbarium specimens. The material from herbaria was hydrated with boiling water and cleared with chloral hydrate for several days; field collected material was fixed in FAA and later preserved in 70% ethanol. Transversal sections of leaves were mounted in glycerin-jelly. For scanning electron microscopy, leaf sections were dehydrated, critical point dried and covered with a gold lamina.Key results: All species contain multicellular uniseriate trichomes which may be glandular or non-glandular. Six basic types of trichomes and two subtypes were identified, which varied according to their position on the leaf; in addition, they show differences in ornamentation and wax deposition. Two types of trichomes and a variant were distinctive of some species; for example, variant 2a1 is characteristic of Senecio jacalensis and occurs in both leaf surfaces, in S. polypodioides type 3d trichomes are present only along the midrib on the abaxial surface, and type 4a trichomes are located only on the leaf margins of S. roseus.Conclusions: The combination of characters like trichome type, ornamentation and wax deposition may be useful for recognizing the species of Senecio section Mulgediifolii.